An analysis lexical cohesion on Ellen Show with Michelle Obama - Krisna, Natalia; Mubarak, Zia Hisni (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
This study applied a discourse analysis study to obtain the types of Lexical Cohesion in YouTube "Ellen Show". The purpose of this study was to analyze the types of lexical cohesion contained in the show. Then, the utterances were analyzed and classified by applying the theory of Halliday & Hasan (1976) to analyze the data source. To get the desired research results, the research method used was descriptive qualitative method. Data collection technique was using observation technique and non-participation technique.The researchers found utterances of lexical cohesion by Michelle Obama and Ellen. As the result of the research, the researchers found 6 types of lexical cohesion, (10) repetition, (4) collocation, (1) synonymy, (0) hyponym, (0) meronymy, (0) antonym. The repetition is the highest type found in the data source, then collocation, and synonymy. Through this research, it is hoped that it can be useful for readers, students, and future researchers. The researchers recommend readers to read this research because this research can help readers to understand lexical cohesion through the reading of reviews of related literature.